The Role of Red Cell Distribution Width in the Diagnosis and Outcome of Neonatal Sepsis in Term Neonates - Al- Omrani, Areej Abdul Abass; Salih, Qamar Ali; Mashallah, Kamal Ismail (Academic Journal of Clinicians, 2025)
Background: Neonatal sepsis is one of the most critical illnesses in newborns with significant morbidity and mortality, particularly in developing countries. Previous studies showed that red blood cell distribution width (RDW) can be used as a prognostic and diagnostic index in various non-hematological diseases. Objective: to evaluate the role of RDW in diagnosis and predicting outcome of neonatal sepsis in term neonates. Patients and Methods: This is a prospective observational study including 75 term neonates with neonatal sepsis and other 50 healthy neonates as controls. The following data were collected :- Mother data included medical and obstetric history, mode of delivery and any prenatal problems; neonatal data including gestational age, sex, clinical presentation; and laboratory assessment in the form of complete blood count, C-reactive protein, blood culture and urine culture. Results: Neonates with sepsis demonstrated higher mean of RDW (17.82±1.38%) than controls (15.62±0.96% with a highly significant difference. The area under the curve (AUC) for RDW was 0.907, 95% CI= 0.847-0.966, p<0.001. The test’s sensitivity and specificity were 92% and 88%, respectively at a cut-off value of RDW= 16.45%. Furthermore, dead neonates had higher mean of RDW (19.46±1.61%) than survived neonates (17.38±0.9%) with a highly significant difference. The AUC of RDW in predicting mortality was 0.852, 95% CI= 0.693-1.0, p<0.001. The test’s sensitivity and specificity were 80% and 93%, respectively at a cut-off value of RDW= 18.55%. Conclusions: The RDW increases significantly in neonatal sepsis compared with healthy neonates. The RDW has a very good diagnostic value in detection of neonatal sepsis with a sensitivity of 92% and specificity of 88%. The RDW could effectively predict mortality in neonatal sepsis with a sensitivity and specificity of 80% and 93%, respectively at cut off value of 18.55%.